A method for preparing a magnetic ion gel thin film gate-intercalated graphene field effect transistor

CN116110794BActive Publication Date: 2026-11-03NANJING UNIV OF POSTS & TELECOMM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310221478.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2026-11-03
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

Existing technologies lack research on using magnetic ion gel films as gate layers for electric field modulation, and traditional solid dielectric materials have limited ability to adjust carrier concentration, making it difficult to achieve high integration and high success rate in the fabrication of field-effect transistors.

Method used

By using a magnetic ion gel film as the gate layer, a strong field effect and high integration are achieved by preparing a metal electrode, transferring a graphene sample and coating it with a magnetic ion gel film, and combining a spin coater and baking process. The device fabrication process is simplified by using a cutting and stacking method.

Benefits of technology

This technology enables efficient electric field control of graphene, resulting in strong electric field effects, uniform and controllable thickness, good mechanical stability and flexibility. This improves the success rate of device fabrication and expands the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116110794B_ABST
    Figure CN116110794B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a magnetic ion gel thin film gate medium graphene field effect transistor, and belongs to the field of two-dimensional material devices and dielectric materials, and comprises the following steps: first, preparing a metal electrode, exposing, developing and fixing a photoresist on a silicon substrate according to a required electrode pattern; evaporating a Ti / Au metal layer to obtain a metal electrode with a target pattern; second, transferring a sample, preparing a standard graphene sample, and transferring the graphene to the silicon substrate with the metal electrode; third, preparing a magnetic ion gel thin film, mixing a magnetic ionic liquid, a polymer and an acetone solvent at a mass ratio of 4:0.9:10, heating and stirring until the mixture is fully dissolved, dropping the mixture on a substrate, and vacuum baking; cutting and covering the magnetic ion gel thin film on the transferred graphene to prepare the magnetic ion gel thin film gate medium graphene field effect transistor. The magnetic ion gel thin film prepared by the method has a uniform and controllable thickness, can provide strong and effective carrier regulation capacity, and simplifies the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of two-dimensional materials and devices and dielectric materials, specifically relating to a method for preparing a magnetic ion gel thin film gate graphene field-effect transistor. Background Technology

[0002] Graphene is a single-atom-layer graphite material with a honeycomb structure. It boasts advantages such as abundant reserves, simple preparation process, and being the thinnest two-dimensional material in the world. Due to the unique structure of graphene, it exhibits many excellent properties, such as extremely high electron mobility at room temperature and high thermal conductivity, demonstrating its enormous potential for device applications.

[0003] Ionic liquids are substances composed entirely of cations and anions (typically organic cations and inorganic anions) that are liquid at room temperature. Liquid gating is an effective tool for controlling carrier concentration, primarily relying on the electric bilayer formed at the dielectric interface. Due to its nanometer-wide gaps, this bilayer can generate a very strong and effective electric field effect. Besides simply enhancing conductivity, the ultra-high carrier concentrations also lead to various interesting phenomena, such as phase transitions, magnetic ordering, and superconductivity.

[0004] The magnetic ionic liquid involved in this invention possesses numerous excellent properties, such as strong carrier control capability, paramagnetism, high thermal stability, corrosion resistance, and a wide electrochemical window. Its strong control capability and paramagnetism are its most significant characteristics. Due to the strong electric field effect, it can effectively control the carrier concentration of the thin film. Its unique paramagnetism allows it to be combined with graphene for multi-field control, inducing magnetism in graphene through the magnetic proximity effect. This allows for the study of the effect and principle of the proximity effect, exploring the changes in properties such as spin-orbit coupling strength and magnetic ordering of graphene. The proximity effect is a type of interfacial effect and a commonly used method for controlling thin film performance, frequently applied in research related to electronic devices. Most reported ionic liquids are composed of non-magnetic cations and anions, such as EMIM [TFSI] and DEME [TFSI]. Currently, non-magnetic ionic liquids can only be controlled by a single electric field and not by multiple fields (magnetic and electric fields). Therefore, magnetic ionic liquids have significant application prospects and value in many fields.

[0005] Magnetic gel films, as a hybrid material, not only retain the original physicochemical properties of magnetic ionic liquids but also solve the inherent mechanical stability problem of magnetic ionic liquids. With the continuous development of science and technology and the increasing demand, their solid form and plasticity fully meet the application requirements, while also greatly expanding the application prospects and value of magnetic ionic liquids. It is worth noting that magnetic ionic gel films retain the intrinsic properties of magnetic ionic liquids very well, such as paramagnetism, strong controllability, high thermal and chemical stability, flexibility, wide electrochemical window, and good corrosion resistance, and their thickness is uniform and controllable.

[0006] Traditional solid-state dielectric materials such as SiO2, Al2O3, and ceramics can play a certain role in regulation, but their ability to adjust carrier concentration is limited. When ionic liquids are used as dielectrics, due to the strong electric field effect of the electric double layer, the carrier concentration can be regulated to 102. 15 cm -2 SiO2 is only 10 13 cm -2 Currently, there are several reports on the manipulation of graphene using non-magnetic ionic liquids. For example, Nongjian Tao et al. used BMIM[PF6] to fabricate graphene-based EDLT devices and measured the relationship between the graphene quantum capacitance and the gate voltage. Iwasa's research group used non-magnetic ionic liquids to manipulate graphene of different thicknesses (1-3 layers) to study the differences in carrier concentration and mobility. At present, there is still a lack of research on the electric field manipulation using magnetic ion gel films as gate layers. In this invention, we adopted an efficient and simple scheme to fabricate magnetic ion gel gate graphene field-effect transistors that possess strong field effects, high integration, and high success rates. Magnetic ion gel films, as gate layers, can provide a very large electric field effect, thereby ensuring high on / off ratio and high conductivity. At the same time, the shearing and stacking operation of the gel films greatly simplifies the device fabrication process and improves the success rate of device fabrication, providing new opportunities for its application in large-scale integrated circuits. Summary of the Invention

[0007] To address the current lack of efficient and simple solutions for the research and fabrication of field-effect transistors (FETs) with strong field effects, high integration, and high success rates using magnetic ion gel films as gate layers for electric field manipulation, this invention provides a method for fabricating magnetic ion gel film gate graphene FETs.

[0008] To achieve the above objectives, the technical solution adopted by this invention is as follows: A fabrication scheme for a magnetic ion-gel gate graphene field-effect transistor includes the following steps: Step 1: Fabrication of metal electrodes: Using photoresist, expose, develop, and fix the silicon substrate according to the desired electrode pattern; deposit a Ti / Au metal layer to obtain a metal electrode with the target pattern; Step 2: Sample transfer: Prepare a standard graphene sample and transfer the graphene onto a silicon substrate with metal electrodes using a transfer platform; Step 3: Fabrication of magnetic ion gel gate graphene field-effect transistor: First, prepare a magnetic ion gel film, cut it and place it on the silicon substrate with metal electrodes from step 2.

[0009] Furthermore, step 1 specifically includes the following steps: Step 1.1: The silicon wafer is ultrasonically cleaned in acetone and ethanol in sequence, then dried with nitrogen gas. The cleaned silicon wafer is then adsorbed onto a spin coater and photoresist MMA EL6 and PMMA A5 are spin-coated in sequence, and then dried on a heated platform. Step 1.2: Place the dried silicon wafer with photoresist into the cavity of the electron beam exposure machine, and bombard the silicon wafer with photoresist using an electron beam to obtain a silicon wafer with the target electrode pattern. Step 1.3: Place the exposed silicon wafer in the developer to remove the photoresist, then place the silicon wafer in isopropanol to fix it, and finally dry it with nitrogen gas; Step 1.4: Place the dried silicon wafer into the cavity of the electron beam evaporation system, evacuate the vacuum, and then deposit titanium and gold in sequence; Step 1.5: Place the vapor-deposited silicon wafer in an acetone solution and let it stand. Peel off the unexposed parts, and the remaining part is the required metal electrode.

[0010] Furthermore, step 2 specifically includes the following steps: Step 2.1: The block graphene is repeatedly pasted with tape and then bonded to the tape with PDMS film. Then, the side of the PDMS with graphene is bonded to the cleaned silicon wafer, and graphene samples that meet the requirements for device fabrication are screened out. Step 2.2: Place the selected graphene sample and the prepared metal electrode on the transfer platform and fix them. Adhere the graphene sample to the PVA and then transfer the graphene sample to the metal electrode channel. Step 2.3: Place the transferred sample into deionized water, immerse it completely and let it stand to remove PVA, and finally dry it with nitrogen gas.

[0011] Furthermore, the method for preparing the magnetic ion gel film is as follows: Step 3.1: Heat and stir the magnetic ionic liquid, polyvinylidene fluoride-hexafluoropropylene, and acetone solvent until the polymer is fully dissolved. After the acetone evaporates, a magnetic ionic gel solution is obtained. Step 3.2: Adsorb the clean substrate onto the spin coater, and drop the magnetic ion gel solution onto the substrate for spin coating to obtain a substrate with magnetic ion gel solution spin-coated; place it in a vacuum oven for baking to remove moisture and excess acetone.

[0012] Furthermore: In step 1.1, the rotation speed of the spin coater is set in steps. The first step is a rotation speed of 4000 rpm for 33 seconds, followed by a rotation speed of 7000 rpm for 8 seconds.

[0013] In step 1.3, the developing time is 35 seconds and the fixing time is 10 seconds.

[0014] In step 1.4, the rate of titanium evaporation is 0.15 Å / s and the thickness is 5 nm, while the rate of gold evaporation is 0.5 Å / s and the thickness is 20 nm.

[0015] In step 3.1, the magnetic ionic liquid is 1-butyl-3-methylimidazolium ferric chloride BMIM[FeCl4].

[0016] In step 3.1, the mass ratio of magnetic ionic liquid, polymer, and acetone solvent required for the preparation of the magnetic ionic gel film is 4:0.9:10, the heating and stirring temperature is 70℃, and the stirring speed is 600 rpm.

[0017] In step 3.2, the baking temperature is 120℃ and the baking time is 40 minutes.

[0018] The magnetic ion-gel thin-film gated graphene field-effect transistor prepared by this invention has the following significant advantages: (1) Strong electric field effect: Magnetic ion gel film can effectively regulate the conductivity of graphene as a gate layer. (2) Paramagnetism: When the magnetic ion liquid is slightly attracted by the magnetic field, it exhibits magnetism, that is, the direction of the magnetization intensity is the same as the magnetic field intensity. (3) Uniform thickness and controllable thickness, which is consistent with the speed of the spin coater. (4) Since the magnetic ion gel film is spin-coated on the silicon wafer, the film can be effectively preserved and reused. (5) Good stretchability. (6) The gel film has good mechanical stability, which solves the problem of easy liquid overflow. (7) The entire preparation process is very efficient, simple and easy to operate. (8) The electrochemical window is above 4V, which supports the development and application of magnetic ion gel film in two-dimensional electronic devices and dielectric fields.

[0019] This invention gels magnetic ionic liquids by selectively dissolving copolymers. The polymer P (VDF-HFP) crystals used are dissolved in acetone, and the polymer dissolved in acetone bridges these crystals, leading to gelation. Adding polyvinylidene fluoride-hexafluoropropylene to the magnetic ionic liquid enhances the flexibility of the magnetic ionic gel. Specifically, the thin film of the magnetic ionic gel achieved by this invention can be directly applied to solid-state devices using a cutting and stacking method. Furthermore, the paramagnetism of the magnetic ionic gel film allows for multi-field manipulation in practical device applications, such as inducing magnetism in non-magnetic metal films through the magnetic proximity effect, greatly expanding the application of magnetic ionic liquids in the device field. The magnetic ionic gel film of this invention has a uniform and controllable thickness, which can be directly achieved by adjusting the spin coater speed.

[0020] The method of this invention greatly reduces the operational difficulty of the entire graphene field-effect transistor fabrication process. A magnetic ion gel film can be directly obtained by drop-casting a magnetic ion gel solution onto a substrate using a dropper, followed by spin-coating and baking. This method is highly efficient and improves operational convenience. Furthermore, while retaining the intrinsic properties and high performance of magnetic ion liquids, its film morphology overcomes the drawback of the free flow of magnetic ion liquids, greatly expanding its application range. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the side gate structure of a magnetic ion-gel thin-film graphene FET. Figure 2 This is a schematic diagram of the electrical detection of a magnetic ion-gel thin-film gate graphene FET. Figure 3 This is a schematic diagram of the dual-layer regulation of EDL electricity; Figure 4 The graph shows the resistance variation of the magnetic ion gel film based on graphene FET in Example 1, controlled by the electric field. Figure 5 This is the IV relationship diagram of the magnetic ion gel thin film gate graphene FET in Example 1; Figure 6 The transfer characteristic curves of the magnetic ion gel film based on graphene FET in Example 1 are controlled by the electric field. Figure 7 The output characteristic curve of the magnetic ion gel film based on graphene FET in Example 1 is a curve showing the electric field modulation. Figure 8 The structure diagram of the magnetic ionic liquid BMIM[FeCl4] in Example 1 is shown. Figure 9 This is a structural diagram of polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)) in Example 1; Figure 10 This is a graph showing the relationship between the magnetic moment of the magnetic ion gel solution and the applied magnetic field in Example 1; Figure 11 This is a photograph of the magnetic ion gel film in Example 1; Figure 12 The graph shows the relationship between the thickness of the magnetic ion gel film and the spin coater speed in Example 1. Implementation

[0022] The present invention will be further explained below with reference to the embodiments.

[0023] This embodiment 1 includes the following steps: Step 1: Prepare the required metal electrode; Step 1.1: The silicon wafers (total thickness 500±15um, oxide layer thickness 285nm) removed from the wafer cassette are cut into 0.8cm×0.8cm pieces and placed sequentially into beakers containing acetone and ethanol. The wafers are then cleaned using an ultrasonic cleaner for 2 minutes, followed by drying with nitrogen. Acetone is used to remove debris, grease, and other contaminants from the wafers, while ethanol is used to remove any residual acetone. The cleaned wafers are then placed on a spin coater, and methyl methacrylate (MMA) EL6 and polymethyl methacrylate (PMMA) A5 photoresists are sequentially spin-coated. The spin coater speed is set in stages: the first stage is at 4000 rpm for 33 seconds, and the second stage is at 7000 rpm for 8 seconds. The wafers are then placed on a heated platform to dry for 2 minutes at 120℃. The drying time depends on the thickness of the MMA and PMMA layers. Step 1.2: Place the dried silicon wafer coated with photoresist into the cavity of the electron beam lithography (EBL) machine and evacuate it to 10°C. -6 Below the Pa level, an electron beam is used to bombard a silicon wafer with photoresist to obtain a silicon wafer with the target electrode pattern. Step 1.3: After exposure, the silicon wafer is placed in the developer to remove the photoresist that has been denatured by the electron beam exposure. Then, the silicon wafer is placed in isopropanol to complete the fixing operation, and finally dried with nitrogen gas. The development time is generally 35s±5s, and the fixing time is 10s±5s. Step 1.4: Place the dried silicon wafer into the cavity of the electron beam evaporation (EBE) system and wait for the cavity to be evacuated to 6×10⁻⁶. -4The deposition rate was below the Pa level. Then, 5 nm of titanium (Ti) and 20 nm of gold (Au) were deposited using electron beam deposition and thermal evaporation, respectively. Titanium primarily served an adhesive function, preventing the gold from failing to adhere properly to the silicon wafer and detaching during subsequent operations. The deposition rate for titanium was 0.15 Å / s, and the deposition rate for gold was 0.5 Å / s. Step 1.5: Place the vapor-deposited silicon wafer into an acetone solution and let it stand for about 10 minutes. Lift off the unexposed parts, and the remaining part is the desired target electrode pattern.

[0024] Step 2: Transfer the sample; Step 2.1: Graphene blocks are repeatedly pasted with tape (mechanical peeling method), and PDMS polydimethylsiloxane film is attached to the tape to obtain PDMS with graphene. Then, the side of PDMS with graphene attached is attached to the cleaned silicon wafer and placed under an optical microscope for observation. Uniform graphene samples that meet the requirements for device preparation are selected. Step 2.2: Place the qualified graphene sample on the sample stage of the transfer platform and fix it. Use the pre-prepared PVA adhesive (polyvinyl alcohol, an adhesive substance) to first adhere the graphene sample to the PVA. Then, place the metal electrode prepared in Step 1 on the transfer stage and fix it. Then, use the transfer platform to transfer the graphene sample on the PVA to the metal electrode channel. The PVA adhesive is synthesized from deionized water and PVA powder. Specific transfer operation: Set the sample stage temperature of the transfer platform to 80℃, press the target sample directly onto the silicon wafer with PVA, and then lower the temperature to 40℃. The PVA can then adhere the target sample. Then, set the sample stage temperature of the transfer platform back to 80℃ and accurately transfer the sample onto the prepared electrode. Maintain the temperature at 80℃ for about 5 minutes to ensure that the PVA remains completely on the silicon wafer. Step 2.3: Place the transferred sample into deionized water, immerse it completely and let it stand for 1-2 hours to remove PVA, and finally dry it with nitrogen.

[0025] Step 3: Prepare magnetic ion gel films; Step 3.1: Weigh 4g of 1-butyl-3-methylimidazolium ferric chloride and 0.9g of polyvinylidene fluoride-hexafluoropropylene and add them to a 25mL beaker. Then weigh 10g of acetone and add it to the beaker. At the same time, add the cleaned magnetic stirrer and cover the entire mouth of the beaker with aluminum foil. Use tweezers to poke several holes in the aluminum foil to allow the acetone to evaporate completely. Then place the beaker on a magnetic stirrer and set the temperature to 70℃ and the speed to 600 rpm. Heat and stir until the polymer is fully dissolved in the acetone. Finally, after the acetone has basically evaporated, a magnetic ion gel solution is obtained. Step 3.2: A clean silicon wafer with an area of ​​1.5cm × 1.5cm is adsorbed onto the spin coater. The magnetic ion gel solution obtained in step 3.1 is then drop-cast onto the substrate using a dropper. The spin coater speed is adjusted according to different thickness requirements. The film thickness follows the rule that the faster the spin coater speed, the thinner the magnetic ion gel film. After spin coatering, a substrate with magnetic ion gel solution spin-coated is obtained. In the experimental data test of this invention, the spin coater speed was set to 2000 rpm and the spin coater time was set to 1 min. The silicon wafer with magnetic ion gel solution spin-coated was placed in a vacuum oven and baked at 120℃ for 40 min to remove moisture and excess acetone. Step 3.3: Cut a small piece of the magnetic ion gel film prepared in step 3.2 with a scalpel, pick it up easily with tweezers and place it on the graphene field-effect transistor in step 2 to obtain the magnetic ion gel gate graphene field-effect transistor. Step 3.4: The instruments used for electrical characteristic testing are a Keithley 2450 dual-channel digital source meter and a Keithley 6487 picoammeter. The source, drain, and gate are represented by S, D, and Gate, respectively.

[0026] The magnetic ion-gel thin-film gate graphene field-effect transistor obtained in this embodiment has the following structural schematic diagram: Figure 1-2 As shown: Figure 1 This is a schematic diagram of the side gate structure of a magnetic ion-gel thin-film graphene FET, where S is the source, D is the drain, Gate is the gate electrode, Si / SiO2 is the silicon substrate, Graphene is the graphene, and Ion-gel is the magnetic ion-gel thin film. Figure 2 This is a schematic diagram of the electrical detection of a magnetic ion-gel thin-film gate graphene FET, where Source is the source electrode, Drain is the drain electrode, and V is the voltage. G —Gate voltage, V D —Source-drain voltage, I D —Source leakage current, at room temperature (25℃), 1×10 5 Pa) The electrical characteristics of the magnetic ion-gel thin-film gated graphene FET were tested using a Keithley 2450 dual-channel digital source meter and a Keithley 6487 picoammeter. The control principle of the magnetic ion-gel thin-film gated graphene field-effect transistor obtained in this embodiment is as follows: Figure 3 As shown: Figure 3 This is a schematic diagram of EDL electrical double-layer regulation, where V G—Gate voltage: Applying a positive voltage to the gate attracts anions from the magnetic ion gel film to accumulate on the gate surface, while repelling cations to the interface between graphene and the gel film, forming two pairs of charged planes. The interval between the anions and cations is only 1 nm. This results in a very strong and effective electric field effect and carrier control capability. The control data of the magnetic ion gel film gate-graphene field-effect transistor obtained in this embodiment are as follows: Figure 4-7 As shown: Figure 4 This is a graph showing the resistance variation of a magnetic ion-gel film based on a graphene FET, modulated by an electric field, where R represents resistance and V represents resistance. G —Gate voltage, Time—Time, the applied voltages are 0.5V and 1V respectively. It can be seen that the resistance of graphene changes significantly when the gate voltage is applied and changed. This is due to the carrier concentration at its channel being regulated by the electric bilayer. Figure 5 The image shows the IV relationship of a magnetic ion-gel thin-film gate graphene FET, where Current represents current, Voltage represents voltage, and slope=2091 indicates that the resistance of this graphene sample is 2091 ohms. This graphene sample is consistent with the previous... Figure 4 The samples are different. The illustration shows that the test uses the four-terminal method to apply current and measure voltage, with the current ranging from -10uA to 10uA in 1uA increments. Figure 6 The figure shows the electric field-controlled transfer characteristic curves of a magnetic ion gel film based on graphene FET, where V G —Gate voltage, V D —Source-drain voltage, I D —Source-drain current, apply a source-drain voltage V of constant magnitude 0.1V. D V G From 3 to -2V, I D An extreme point appeared at the gate voltage of 2.8V. This is because the PVA used in this experiment to transfer graphene requires the use of deionized water. The water molecules and oxygen attached to the surface of graphene will bind the free electrons in the orbitals and exhibit reducing electron transfer. Holes will be generated at the corresponding positions, resulting in p-type doping. Figure 7 To obtain the output characteristic curves of the magnetic ion gel film based on graphene FET, a fixed gate voltage was applied with values ​​of 1, 3, -1, and -2 V. D The source-drain current I changes from 0 to 100mV as the gate voltage changes. D Significant changes occurred. The intrinsic properties of the magnetic ion-gel thin-film gate graphene field-effect transistor obtained in this embodiment are as follows: Figure 8-12 As shown: Figure 8The diagram shows the structure of the magnetic ionic liquid BMIM[FeCl4] in Example 1. [BMIM]FeCl4 is prepared by mixing [BMIM]Cl crystal powder with two types of ferric chloride (anhydrous FeCl3 and FeCl3·6H2O). Due to its rich iron content and low cost, the preparation price of the magnetic ionic liquid BMIM[FeCl4] is relatively lower than that of ordinary ionic liquids. Figure 9 The diagram shows the structure of polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)) in Example 1, which is soluble in acetone and can gel magnetic ionic liquids. Figure 10 The graph shows the relationship between the magnetic moment and the applied magnetic field of the magnetic ion gel solution in Example 1, where Magnetic moment is the magnetic moment and Magnetic field is the magnetic field, ranging from -10000 Oe to 10000 Oe (-1T to 1T). The magnetic moment of the solution is linearly related to the magnetic field, and the inset shows its response to the magnet. This fully demonstrates that the magnetic ion gel solution is paramagnetic. Figure 11 This is a photograph of the magnetic ion gel film in Example 1, which can be easily picked up with tweezers; Figure 12 The graph shows the relationship between the thickness of the magnetic ion gel film and the spin coater speed in Example 1, where Thickness is the film thickness and Speed ​​is the spin coater speed. The spin coater speed can be selected according to different thickness requirements. The film thickness and the spin coater speed follow the rule that the faster the speed, the smaller the thickness of the magnetic ion gel film.

[0027] As can be seen from the ten figures above, the graphene field-effect transistor obtained in this embodiment uses a magnetic ion-gel film as the gate layer, which exhibits a very strong carrier control capability over graphene, specifically manifested in the degree of change in resistance or current value with gate voltage. This embodiment also fully demonstrates the significant characteristics of the magnetic ion-gel film, such as paramagnetism, controllable thickness, high independence, flexibility, and high mechanical stability. In summary, due to its numerous unique and outstanding properties, this provides new opportunities for its application in two-dimensional electronic devices, electrolytes, and integrated circuits. Through the above embodiments, we have successfully completed the currently lacking research on electric field control using magnetic ion-gel films as gate layers. Furthermore, based on this, we have successfully fabricated a magnetic ion-gel gate graphene field-effect transistor with strong field effect, high integration, and high success rate using an efficient and simple scheme.

[0028] The above description is merely a preferred embodiment of the present invention. The aforementioned magnetic ion adhesive film is a specific example and does not constitute any limitation on the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, such as changes in device structure, type of magnetic ion liquid, type of polymer, and chemical ratio. These improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a magnetic ion-gel thin-film gated graphene field-effect transistor, characterized in that, Includes the following steps: Step 1: Prepare a metal electrode; Step 2: Prepare a standard graphene sample and transfer the graphene sample to a silicon substrate with a metal electrode using a transfer platform; Step 3: Prepare a magnetic ion gel film and cut it, then place it on the graphene field-effect transistor obtained in Step 2; wherein, the preparation of the magnetic ion gel film includes: mixing a magnetic ionic liquid, a polymer, and an acetone solvent in a mass ratio of 4:0.9:10, wherein the magnetic ionic liquid is 1-butyl-3-methylimidazolium tetrachloride ferric chloride BMIM[FeCl4], and the polymer is polyvinylidene fluoride-hexafluoropropylene P (VDF-HFP), heating and stirring at 70°C and 600 rpm until the polymer is fully dissolved, and obtaining a magnetic ion gel solution after the acetone evaporates; drop casting the magnetic ion gel solution onto a substrate and homogenizing it, then baking it in a vacuum oven at 120°C for 40 minutes to remove moisture and excess acetone, thereby obtaining the magnetic ion gel film.

2. The method for preparing the magnetic ion-gel thin-film gate graphene field-effect transistor according to claim 1, characterized in that, Step 1 includes: ultrasonically cleaning the silicon wafer in acetone and ethanol in sequence and drying it with nitrogen gas; spin-coating photoresist MMA EL6 and PMMA A5 in sequence and drying it; obtaining the target electrode pattern by electron beam exposure; after development, isopropanol fixing and drying with nitrogen gas, depositing titanium and gold in sequence; and placing the deposited silicon wafer in acetone for peeling to obtain the metal electrode.

3. The method for preparing a magnetic ion-gel thin-film gated graphene field-effect transistor according to claim 1, characterized in that, Step 2 includes: repeatedly pasting the block graphene with tape, and bonding it to the tape with a PDMS film; attaching the side of the PDMS with graphene to the cleaned silicon wafer and screening the graphene samples; pasting the screened graphene samples onto PVA and transferring them to the metal electrode channel using a transfer platform; immersing the transferred samples in deionized water to remove PVA and drying them with nitrogen gas.

4. The method for preparing a magnetic ion-gel thin-film gated graphene field-effect transistor according to claim 2, characterized in that, When spin-coating photoresist, the first step involves a rotation speed of 4000 rpm for 33 seconds, followed by a rotation speed of 7000 rpm for 8 seconds.

5. The method for preparing a magnetic ion-gel thin-film gate graphene field-effect transistor according to claim 2, characterized in that, The developing time is 35 seconds, and the fixing time is 10 seconds.

6. The method for preparing a magnetic ion-gel thin-film gated graphene field-effect transistor according to claim 2, characterized in that, The vapor deposition rate of titanium is 0.15 Å / s and the thickness is 5 nm, while the vapor deposition rate of gold is 0.5 Å / s and the thickness is 20 nm.

7. The method for preparing a magnetic ion-gel thin-film gated graphene field-effect transistor according to claim 1, characterized in that, When preparing the magnetic ion gel film, a clean silicon wafer with an area of ​​1.5 cm × 1.5 cm is used as the substrate, the magnetic ion gel solution is drop-cast onto the substrate, and homogenized at 2000 rpm for 1 minute.

8. The method for preparing a magnetic ion-gel thin-film gated graphene field-effect transistor according to claim 1, characterized in that, The spin coating rate should be selected according to the required film thickness. The faster the spin coating rate, the smaller the thickness of the resulting magnetic ion gel film.

9. The method for preparing a magnetic ion-gel thin-film gated graphene field-effect transistor according to claim 3, characterized in that, The graphene samples were prepared by mechanical exfoliation, and single-layer graphene samples with uniform thickness were selected.

10. The method for preparing a magnetic ion-gel thin-film gated graphene field-effect transistor according to claim 3, characterized in that, After transfer, the sample is completely immersed in deionized water for 1-2 hours to remove PVA, and then dried with nitrogen.

Citation Information

Patent Citations

  • Preparation method of independent ionic gel film gated graphene field effect transistor

    CN114695124A